Dawr al-Ṭibāʻah al-ʻUmānīyah fī al-Taʻrīf bi-al-Quṭb Aṭfayyish - Ḥalāsah, ʻAmmār (al-Muʼtamar al-Duwalī al-Khāmis bi-Mālīziyā: Ḥarakat al-Ṭibāʻah al-ʻUmānīyah wa-Atharuhā fī al-Tawāṣul al-Ḥaḍārī, 2018)
Shaykh al-Quṭb Aṭfayyish was able, through the extraordinary scholarly capacities granted him, to write in more than one specialism, to command more than one science, and to compose in most of the legal and linguistic sciences — which made his juristic and religious works, and his linguistic works, the object of attention for students in every region of the world. Omani presses played the largest part in making this towering figure known and in placing his writings within reach of every student in the east and west of the earth. To what extent, then, have the Omani publishing houses contributed to encompassing this scholarly legacy? That is the question this paper attempts to answer.
MHF-PRINT2018-018
Keywords: al-Quṭb Aṭfayyish; Omani printing; Publishing houses; Ibāḍī scholarship; Book circulation